A recontextualização das competências no currículo do Curso Técnico em Eletrônica do Instituto Federal Sul-rio-grandense Campus Pelotas e a reforma da Educação Profissional - Palau, Roberta de Carvalho Nobre (2013)
This dissertation reports the results of an investigation which aimed to analysis the recontextualization process about the competencies insertion in the curriculum of the Electronics Technician Course at the Sul-rio-grandense Federal Institute from Pelotas Campus since the implementation of 2.208/1997 Decree. The intention was verify which changes occurred on the curriculum course and what really the competence concept brought to the teachers pedagogical organization in the pedagogical practice context. The research was based on a qualitative methodology and used as investigation instruments a closed questionnaire, an interview with eight teachers besides a document analysis which involve a period between 1997 and 2010. The discussions and the data analysis were done based on the Basil Bernstein and Stephen Ball theories. Among the main results highlight the fact that the Electronics Technician Course teachers present a strong resistance against the competencies which is justified by them on the interview about the way it was introduced in Professional Education imposed by law and consequently by their own school. Was verified that although the competencies have brought these curricular changes, that one when was shifted from the policy production context to the school context they were broadly discussed and resignificated on the institution, in the curriculum course and as well in the teachers pedagogical organization.